Exposição ocupacional a pesticidas afeta respostas imunológicas antitumorais fundamentais em mulheres com câncer de mama estratificadas como risco intermediário de recorrência - Silva, Janaína Carla da (2022)
Breast cancer is a disease whose clinicopathological characteristics are of great importance to predict the prognosis and guide clinical interventions. Risk stratification of death and recurrence is a strategy to guide therapeutic decisions, and is divided into low, intermediate or high risk. Both low and high risk are based on well-defined clinical parameters, while intermediate risk is a challenge for the clinician as it has many other conditionals, which can result in undertreatment, increasing the chances of recurrence or even overtreatment, which can lead to systemic damage. Little is known about the influence of environmental factors, such as occupational exposure to pesticides, on breast cancer risk stratification, especially in relation to the intermediate stratum. Considering that most breast cancer patients treated in the Southwest region of Paraná present intermediate risk, and that they present significant occupational exposure to pesticides, the present study aims to analyze whether occupational exposure to pesticides in women with breast cancer may alter the risk stratification of the intermediate stratum. This study included women diagnosed with breast cancer treated at Hospital do Câncer Francisco Beltrão (Ceonc), Francisco Beltrão, Paraná, Brazil. All patients signed an informed consent form and the study was authorized by the Institution's Research Ethics Committee under number 35524814.4.0000.0107. Patients were stratified as recommended by the Ministry of Health (Joint Ordinance No. 4) considering the following criteria: affected lymph nodes, tumor size, histological grade, estrogen and progesterone receptors, molecular subtype and age at diagnosis. Based on risk stratification and pesticide exposure data, patients were categorized as intermediate risk/pesticide exposed, intermediate risk/nonpesticide exposed, high risk/pesticide exposed, and high risk/non-pesticide exposed. To investigate the inflammatory profile, the levels of tumor necrosis factor alpha (TNF-α), interleukin 4 (IL-4), interleukin 17A (Il-17A) and interleukin 12 (IL-12) were quantified using the enzyme immunoassay method. The oxidative stress profile was also evaluated by measuring the levels of hydroperoxides, the plasma total antioxidant capacity (TRAP), and the nitric oxide metabolites (NOx). The tumor expression of cytotoxic T lymphocyte-associated protein 4 (CTLA-4), transforming growth factor beta 1 (TGF-β 1) and inducible nitric oxide synthase enzyme (iNOS) were also evaluated by immunofluorescence. The general clinicopathological profile of the patients showed a predominance of more aggressive tumor subtypes, including luminal B and triple negative, as well as tumor sizes greater than 2 cm. The results referring to the risk stratification profile, demonstrated to follow the current standard procedure of stratification. The analysis of the oxidative and antioxidant profile did not show significant differences, while a significant reduction of IL-12 was observed in patients at intermediate risk when compared to the unexposed group. In the analysis of tissue markers, an increase in the expression of iNOS and TGF-β1 was observed in the immunologic infiltrate. CTLA-4, on the other hand, showed an increase in expression in the infiltrate and a reduction of expression in tumor cells. Considering the relevance of IL-12 in antitumor responses, as well as the tissue markers investigated here (iNOS, TGF-β1 and CTLA-4), our data indicate that breast cancer patients classified as intermediate risk exposed to pesticides may benefit from a re-stratification to high risk.